Hubungan Pengetahuan dengan Sikap Ibu Hamil Primigravida tentang Persiapan Persalinan di BPM Ny “E” Desa Serangan Kecamatan Mlarak Kabupaten Ponorogo. - Eliya Rohmah; Suprijati Suprijati; Titik Susanti (Jurnal Delima Harapan, 2017)
Based on the preliminary study in BPM Ny "E" Serangan Village, Mlarak Subdistrict,Ponorogo Regency got problem that mother came to BPM with complete openingand did not bring delivery preparation. To overcome these problems it is necessary tomake improvements in information about the preparation of labor through midwives,doctors, mass media and others. This study aims to determine the relationship ofknowledge and attitudes primigravida about labor preparation in BPM Ny. "E" SeranganVillage, Mlarak Sub-district, Ponorogo Regency.This research was analytic with correlation approach, cross sectional researchdesign, this research was conducted at BPM Ny "E" Serangan Village, Mlarak Subdistrict,Ponorogo District, from January to February 2017. Population were allprimigravida pregnant women in January -February 2017 with the number 30, thesample with the amount of 30 with the sample total sampling. Independent variable is theknowledge of pregnant women pimigravida about delivery preparation and dependentvariable is attitude of pregnant woman pimigravida about delivery preparation. Theresearch instrument used questionnaire. Statistical test by using Spearman Rank at asignificant level of 0.05.Based on the results of research in the knowledge of labor preparation most ofthe respondents are 18 (60%) knowledgeable less. Attitudes about the preparation ofchildbirth almost all respondents ie 24 (80%) with a negative attitude. There is arelationship of knowledge with attitude of primigravida pregnant mother about laborpreparation, with Sperman Rank statistic test get p value 0,001 <α 0,05 so H1 acceptedand H0 rejected. With Coefficient Correlation 0.555 which means there is a moderaterelationship.From the results of this study is expected to play an active role in followingeach counseling so that it can add information and improve the ability to makepreparations for childbirth as well as understand the importance of preparation of labor,and for health workers to increase the efforts of health services primigravida, especiallycounseling about the preparation of labor so that it can improve pengtahuanprimigravida about labor preparation.